Sistem Pendukung Keputusan Pemilihan Smartphone Menggunakan Metode SAW Berbasis Web - Irmawati Carolina; Aryani Rahayu (LPPM Universitas Bina Sarana Informatika, 2026)
The rapid development of information technology has led to an increase in the production and diversity of smartphones available in the market. This condition often makes it difficult for consumers to select smartphones that meet their needs and budget constraints. To support this decision-making process, a system capable of providing objective recommendations based on measurable criteria is required. This study aims to develop a web-based Decision Support System (DSS) by implementing the Simple Additive Weighting (SAW) method for smartphone selection. The SAW method is chosen due to its ability to generate rankings that are simple, efficient, and easy to understand. The criteria used in the system include RAM, battery capacity, internal storage, camera quality, price, and performance score (Antutu). Smartphone data are obtained from reliable secondary sources. The implementation results indicate that the system is capable of presenting smartphone recommendations based on the highest preference values in accordance with the predefined criteria weights. This system is expected to assist users in obtaining more rational and structured information when determining the most suitable smartphone choice.